A cluster epidemic of influenza A(H1N1)pdm09 virus infection in four captive cheetahs (Acinonyx jubatus). (11th February 2021) - Usui, Tatsufumi; Ueda, Miya; Azumano, Akinori; Nomura, Mika; Arima, Toru; Murata, Koichi; Ito, Toshihiro; Yamaguchi, Tsuyoshi
Abstract: In January 2019, four cheetahs ( Acinonyx jubatus ) kept at a Japanese zoo intermittently showed respiratory signs following the incidence of seasonal influenza in animal caregivers. Respiratory materials (saliva, sputum and food tray swabs) were non‐invasively collected from the four cheetahs. Although we were unable to isolate the virus, the NP gene of influenza A virus was detected in three of the cheetahs but not in the fourth cheetah that had nearly recovered. From a food tray swab which tested weakly positive by a commercial influenza detection kit, we were able to obtain the whole‐genome sequence of the influenza A virus. Analysis of the genome, A/cheetah/Kanagawa/2/2019(H1N1), revealed that the virus was closely related to influenza A(H1N1)pdm09 viruses isolated from humans in Japan in the 2018–2019 winter. Production of haemagglutinin inhibition (HI) antibodies (64–128 HI) against an A(H1N1)pdm09 virus in plasma samples confirmed infection of all four cheetahs. The animals continued to produce antibodies for at least 314 days after disease onset. These findings strongly suggest that reverse zoonotic transmission of A(H1N1)pdm09 virus occurred from human to cheetah and subsequently from cheetah to cheetah in the zoo. We also show that specimens can be safely and non‐invasively collected from non‐domesticated animals and used to investigate respiratory infectious diseases.